THE STUDENTS’ ACHIEVEMENT IN PRONOUNCING ENGLISH SONG USING SMULE APPLICATION - Himatul Khoiriyah; Ahmad Mustamir Waris; Juhansar Juhansar (Indonesian EFL Journal, 2019)
The development of science and technology forces academics to be more creative in the teaching- learning process to achieve a better quality of education. Smule application as a part of science and technology development should be used effectively and creatively as a tool in that process especially in English education field. Therefore, this research aims at describing the students’ achievement in pronouncing English song using Smule application and finding out the factors influencing students’ achievement in pronouncing English song using Smule application. This research used quantitative data with descriptive statistical approach. The data were collected through English pronunciation test and questionnaire. The English pronunciation test was used to collect the data related to students’ English pronunciation achievement and the questionnaire was used to find out the factors influencing students’ English pronunciation achievement. The results showed that the mean score of students’ achievement in pronouncing English song using Smule application was 3.81 or almost good. It was influenced by the low frequency in practicing pronunciation, the difficulty to balance singing karaoke and music instruments on fast song tempo, and the lack of using Smule application to sing karaoke.Keywords: achievement; English song; pronunciation; smule application; university students.